Security of industrial control systems and cyber physical systems : first Workshop, CyberICS 2015 and First Workshop, WOS-CPS 2015 Vienna, Austria, September 21-22, 2015 Revised selected papers /: first Workshop, CyberICS 2015 and First Workshop, WOS-CPS 2015 Vienna, Austria, September 21-22, 2015 Revised selected papers. (2016) - Unknown
No abstract available